3x-6x=7x+1

Simple and best practice solution for 3x-6x=7x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-6x=7x+1 equation:



3x-6x=7x+1
We move all terms to the left:
3x-6x-(7x+1)=0
We add all the numbers together, and all the variables
-3x-(7x+1)=0
We get rid of parentheses
-3x-7x-1=0
We add all the numbers together, and all the variables
-10x-1=0
We move all terms containing x to the left, all other terms to the right
-10x=1
x=1/-10
x=-1/10

See similar equations:

| 8.23(3q+6)=8 | | 2t-32=2 | | 1÷2(4x-2)=-12 | | 7+16y=11y | | 21-0.25x=7 | | W=6×3.14×b | | -7g+41+6g=3g | | 7(x–15)=28 | | 100+12h=23+12h | | 9+4k=13 | | 14h-12h-h-1=15 | | -3x-6=7x+1 | | 130+.2x=70+.6x | | 2(3x+1)=-3(x-8) | | 5x-5x-12=25 | | 2/33x-6=4x-2 | | f/3=-1 | | -1/3=1/6v-7/9 | | 19x+15=8x | | 281=-6-7(1+6b) | | 146+(5x+3)+(4x+8)=180 | | 2(4+k)=-k+8 | | -12/n=4 | | x=-2*(x+7) | | .1/4y-3=5-2y | | .14y-3=5-2y | | 5*2x=3x+1 | | 9x+12+23=13x+7 | | 2(4w-1)=-10(w-3+4 | | -2(5u-5)+2u=2(u+2) | | 8x-14x+-7=11 | | -2(2w-7)+10w=34 |

Equations solver categories